A novel procedure in combination of genomic sequencing, flow cytometry and routine culturing for confirmation of beer spoilage caused by Pediococcus damnosus in viable but nonculturable state. (15th January 2022) - Xu, Zhenbo; Wang, Kan; Liu, Ziqi; Soteyome, Thanapop; Deng, Yang; Chen, Ling; Seneviratne, Gamini; Hong, Wei; Liu, Junyan; Harro, Janette M.; Kjellerup, Birthe V.
Abstract: Spoilage bacteria had been shown to form viable but nonculturable (VBNC) state maintaining food spoilage capability. In this study, a novel procedure was used to confirm a beer spoilage case caused by a Pediococcus damnosus strain in the VBNC state. Firstly, flow cytometry, routine culturing and PMA-PCR methods were used to identify approximately 10 3 cells/ml VBNC cells in the spoiled beer sample based on the difference between CFU and viable cell numbers. Secondly, genomic sequencing showed all acquired scaffolds were identical to the genome of P. damnosus with no existence of other species or isolates. In addition, VBNC cells were obtained in both simulation conditions, including beer low temperature storage and subculturing. MRS agar supplemented with catalase was found to resuscitate VBNC cells. Normal, VBNC and resuscitated cells showed similar level of beer spoilage capability. As concluded, a novel procedure, in combination of genomic sequencing, flow cytometry and routine culturing was used to confirm VBNC cells in spoiled beer sample, providing direct evidence on the beer spoilage caused by VBNC P. damnosus cells, and will aid in further study on VBNC state in food industry so that more evidence on food safety problem caused by VBNC microbes will be shown. Highlights: This is the first report on beer spoilage caused by VBNC state P. damnosus. VBNC state was induced by beer subculturing and low temperature. MRS agar supplemented with catalase was found to induce the resuscitation of VBNC cells. Normal, VBNC and resuscitated cells showed similar level of beer spoilage capability.